Transforming the rule of law into a welfare state: constitutional perspectives on social assistance policy - Ida Tutia Rakhmi; Auzan Qasthary; Chairul Bariah; Intan Munirah; Rifka Safira (Geuthèë Institute, Aceh, 2026)
The transformation of the Negara Hukum into a welfare state positions social assistance policies as a strategic instrument for fulfilling citizens’ rights. However, in practice, the implementation of social assistance in Indonesia faces significant challenges, including mistargeting, weak accountability, and regulatory disharmony. This study aims to analyze the conformity of social assistance policies with the principles of the rule of law and to reconstruct an ideal policy model. The research employs a normative juridical approach through the analysis of legal frameworks, particularly the Undang-Undang Dasar 1945, as well as relevant legal doctrines and literature. The findings indicate that although social assistance policies possess strong constitutional legitimacy, their implementation reveals a gap between normative expectations and practical realities. Therefore, policy reconstruction is required through a rights-based approach, integrated data system reform, regulatory harmonization, and strengthened multi-level oversight. In conclusion, social assistance must be treated as a constitutional right managed with transparency and accountability. This study recommends strengthening regulatory frameworks, digitalizing data systems, and enhancing public participation as strategic measures for policy improvement.